Dietary diversity score and socio-economic factors of stunting among pre-school children in Rajshahi city, Bangladesh (Journal of Bio-Science, 2019)
In the developing countries, stunting has been the most tenacious public health problem and is the major cause of child mortality and global disease burden, where 80% of this burden is found in developing countries and would result in 22% loss of adult income. The aim of this study was to investigate prevalence and determinant factors associated with stunting among pre-school children in Rajshahi City, Bangladesh. A multi-stage cross sectional study was performed during the period March 2017 to September 2017. One thousand and nine (1009) pre-school children (36≤ Age ≤71 months) were considered as our study population. Data were collected by using a pretested and semi-structured questionnaire, which consisted of socio-economic characteristics, dietary and feeding pattern related information. Stunting of a child was determined using the WHO Multicenter Growth Reference Standard. Chi-square test and multiple logistic regressions were carried out to identify determinants of stunting. The odds ratio (OR) with a 95% confidence interval was calculated to assess the strength of the association, and p-value of